Essential metabolic, anti-inflammatory, and anti-tumorigenic functions of miR-122 in liver - Hsu, Shu-hao; Wang, Bo; Kota, Janaiah; Yu, Jianhua; Costinean, Stefan; Kutay, Huban; Yu, Lianbo; Bai, Shoumei; La Perle, Krista; Chivukula, Raghu R.; Mao, Hsiaoyin; Wei, Min; et al. (The Journal of clinical investigation, 2012)
miR-122, an abundant liver-specific microRNA (miRNA), regulates cholesterol metabolism and promotes hepatitis C virus (HCV) replication. Reduced miR-122 expression in hepatocellular carcinoma (HCC) correlates with metastasis and poor prognosis. Nevertheless, the consequences of sustained loss of function of miR-122 in vivo have not been determined. Here, we demonstrate that deletion of mouse Mir122 resulted in hepatosteatosis, hepatitis, and the development of tumors resembling HCC. These pathologic manifestations were associated with hyperactivity of oncogenic pathways and hepatic infiltration of inflammatory cells that produce pro-tumorigenic cytokines, including IL-6 and TNF. Moreover, delivery of miR-122 to a MYC-driven mouse model of HCC strongly inhibited tumorigenesis, further supporting the tumor suppressor activity of this miRNA. These findings reveal critical functions for miR-122 in the maintenance of liver homeostasis and have important therapeutic implications, including the potential utility of miR-122 delivery for selected patients with HCC and the need for careful monitoring of patients receiving miR-122 inhibition therapy for HCV.